Overview of Communication Activities and a Plan to Improve Public Perception of Food Additives - Starman, Ana; Mičović, Elizabeta; Langerholc, Tomaž (Agricultura Scientia, 2023)
Food additives are considered a high-risk factor by the EU and Slovenian consumers, although they are strictly regulated by the authorities and pose a low risk to consumers. However, risk communication about food additives is challenging and involves the interactive exchange of information about hazards, taking into account the risk perception of the target groups. A plan for communication activities aimed at improving public perception of food additives was structured based on the review of scientific literature and the overview of previous communication efforts communicated by various information sources to raise awareness among the Slovenian public from January 2015 to January 2022. The overview included governmental and nongovernmental organizations that are credible sources of information on food safety for Slovenian consumers at the national and EU level. The objective was to develop an effective communication plan on food additives with defined objectives, target groups, key communication messages, communication activities, tools, and channels. The proposed plan can serve as a good basis for launching an effective awareness campaign on food additives to reduce public concern and improve the knowledge of average consumers about the use of additives in food.